2007
DOI: 10.2215/cjn.03691106
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Progression from Microalbuminuria to Proteinuria in Patients Who Have Type 1 Diabetes and Are Treated with Angiotensin-Converting Enzyme Inhibitors

Abstract: The aims of this study were to assess the frequency and determinants of (1) treatment with angiotensin-converting enzyme inhibitors (ACE-I) and (2) progression to proteinuria in the presence of ACE-I treatment in patients with type 1 diabetes and microalbuminuria. A clinic-based cohort study of patients with type 1 diabetes was begun in 1991. The patients who were included in this study (n ‫؍‬ 373) are the cohort members who received a diagnosis of microalbuminuria during a 2-yr baseline observation and were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
3
32
0
Order By: Relevance
“…Also the single determination of ACEI/ARB treatment might not be sufficient to detect a statistically significant effect of these drugs on risk of ESRD. However, incorporating changes over time in usage of these drugs, as we have done previously, 30 most likely would not change our findings.…”
Section: Discussionmentioning
confidence: 84%
“…Also the single determination of ACEI/ARB treatment might not be sufficient to detect a statistically significant effect of these drugs on risk of ESRD. However, incorporating changes over time in usage of these drugs, as we have done previously, 30 most likely would not change our findings.…”
Section: Discussionmentioning
confidence: 84%
“…Thus, reduction of albuminuria is a major target for renoprotective therapy in both type 1 and type 2 diabetes. Clinical studies have demonstrated that ACEIs and ARBs can reduce albuminuria in diabetic patients; however, not all patients respond to the treatment (44), in many cases because of incomplete blockade of the RAS. Vitamin D also has antiproteinuric activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although rates of complications appear to have declined substantially over the past 2 decades, such improvements may not apply to the rates of ESRD (3). Furthermore, despite advances aimed at improving glycemic control and inhibiting deleterious neurohormonal pathways, such as the renin-angiotensin-aldosterone system (RAAS), evidence from population databases and clinical trials imply that the incidence of DN has been postponed but not outright prevented (4)(5)(6)(7). Finally, the overall prevalence of DN continues to increase in proportion to the rising prevalence of diabetes (3,8).…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have explored the causal relationship between cardiac autonomic neuropathy and renal impairment (6,12,(17)(18)(19). In the nondiabetic population, the Atherosclerosis Risk in Communities studywhich followed 13,241 adults, 12% of whom had baseline type 2 diabetes-demonstrated that low HRV was associated with the subsequent development of ESRD and CKDrelated hospitalization after 16 years of follow-up (17).…”
Section: Introductionmentioning
confidence: 99%